EVALUASI TERHADAP PEMBINAAN GURU MELALUI SUPERVISI PENDIDIKAN - Eva Mustafiah (Bajang Institute, 2022)
Supervision of education can be seen in the long term results. While the results of the supervision of education that can be known quickly only the appearance of temporary results. And this will cause us difficulties in evaluating the program of educational supervision, given the scope to be supervised is very broad, (teachers, school staff, school program is the target of evaluation of education supervision program)